2015
DOI: 10.4236/ajps.2015.61012
|View full text |Cite
|
Sign up to set email alerts
|

Root Morphology and Anatomy of Field-Grown Erianthus arundinaceus

Abstract: Erianthus species are perennial C4 grasses with such high biomass productivity and high tolerance to environmental stresses that they can be grown in marginal land to supply raw material for cellulosic bioethanol. Because high biomass production and strong tolerance to environmental stresses might be based on their large and deep-root system, we closely examined the morphology and anatomy of roots in first-year seedlings of field-grown Erianthus arundinaceus. The deep-root system of E. arundinaceus consists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…At above the junction, the cortical cell layer becomes invisible when the endodermis gradually merges with mucilage (Figure 2D ). Most plant species exhibit positive correlations between the root diameter and the thickness of cortex cell layer (Figure 4A ; Gu et al, 2014 ; Kong et al, 2014 ; Shiotsu et al, 2015 ). With assuming that the root diameter and cortical thickness are linearly correlated, the slopes of the fitting lines for several plant species were comparatively estimated by using a linear regression model ( p < 10 −4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At above the junction, the cortical cell layer becomes invisible when the endodermis gradually merges with mucilage (Figure 2D ). Most plant species exhibit positive correlations between the root diameter and the thickness of cortex cell layer (Figure 4A ; Gu et al, 2014 ; Kong et al, 2014 ; Shiotsu et al, 2015 ). With assuming that the root diameter and cortical thickness are linearly correlated, the slopes of the fitting lines for several plant species were comparatively estimated by using a linear regression model ( p < 10 −4 ).…”
Section: Resultsmentioning
confidence: 99%
“…(B) Comparisons of the ratios of cortical cell thickness to root diameter with those of other plant species. Data were collected from Gu et al ( 2014 ), Kong et al ( 2014 ), and Shiotsu et al ( 2015 ). The error bars indicate standard deviations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shiotsu et al . () observed that E. arundinaceus accumulates starch grains in the pith of steles from autumn to winter. In the present study, shoot growth increased (Figure ) with increasing atmospheric temperature from April to May (Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Erianthus arundinaceus exhibits excellent soil-derived stress tolerance including acid tolerance (Matsuo et al 2002), drought tolerance (Matsuo et al 2002, Augustine et al 2015, Manoj et al 2019, salt tolerance (Manoj et al 2019), and nematode resistance (Stirling et al 2011;Bhuiyan et al 2014). In addition, specific structural characteristics (e.g., thick diameter and soil sheath) and chemical components (lignin, phenolic compounds, and starch) have been identified in the roots of E. arundinaceus (Matsuo et al 2002, Fukuhara et al 2013, Shiotsu et al 2015, which are possibly associated with its soil-derived Takaragawa H, Matsuda H and Terajima Y 2023 Acidic soil tolerance of sugarcane and Erianthus root assessed by cell membrane stability. Plant Root 17: 26-35.…”
Section: Introductionmentioning
confidence: 99%